Real-time VideoMail for IP-based videophone system - Ortega, Jerome C.
Current implementations of video mails limit the user to store video messages in a remote server. This, however, adds recurring expenses for the user because of subscriptions for the remote servers. Moreover, it does not allow videophone users to interrupt video message recording. This interruption is important for just-in-time calls so that return calls may not be necessary. This paper proposes a video mail application for an IP-based videophone that will allow videophone users to see the video message while being recorded even if the video-phone is unattended. With this, a video-based caller identification can be implemented to provide another layer of security for the users. By co-locating the video mailbox with the videophone, monthly server maintenance fees can be cut down.